(3OjhGf GdCOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s
(3ChdgG (B:s
(3ef HGH GdeaGYdI hgh eG RjO Hjf GdaGA efg hGdYjf Cda LGPHg GdTF Ci fGRYg EjGg, hLGfHg Ci JQc eNGWdJg , hMGQHg ef GdMQH , hMGSHg ef GdMSGH s
(3BNQgG (B:s
(3ef HGH GdJaGYd bhdg JBNjG ef GdENGA hef GdegehR YLRkG JMGSHhG HGdMLGQI Ci JQGehGHgG hef GdeKGd W JhGWDG Ydi GdCeQ Ci GJabhG HGH GdaYddI s
(3GdLRA GdKGfi ef GdfSNI GdSGHbI (B" (3SgSHdG (B- (3GjQGf (B829 "s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B293s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GddZIs